Good leader and effective leadership / Hafizah Md Aris, Norsyuhada Mohd Hanafi and Shantie Mohamad - Md Aris, Hafizah; Mohd Hanafi, Norsyuhada; Mohamad, Shantie (Faculty of Information Management, 2014)
This article discusses about various matters related to leadership which is stressed on steps of leadership plan, characteristics of a good leader, and also categories of the leadership. These elements contained in this paper are basically talk on what a leader should have and follow to become a good leader with an effective leadership.